Registration of Physical Development Indices in School Physical Education: Proposal of a Documentation Package in Compulsory Education - Danis Απόστολος (Inquiries in Physical Education and Sport, 2014)
Motor efficiency, physical activity and body composition of schoolchildren characterize their physical development, which is the result of musculoskeletal growth and nutrition, as well as the influence of exogenous factors that are formed in family, in socio-cultural environment and in school. The introduction of physical development indices for the control of physical sufficiency and of balanced development of schoolboys and schoolgirls is directly linked to their physical and mental health and to the prevention of chronic diseases. The evaluation of these indices is also an additional educational process that is combined with the creation of incentives for achieving specific objectives in motor performance and attitudes to physical activity/exercise and nutritional habits. For the evaluation of the physical development of schoolchildren, a handy, valid and reliable package for school fact is suggested, which includes two indices for the motor efficiency (performance in standing broad jump test and sit and rich test), one index for physical activity (average time of daily physical activity) and one index for body composition (body mass index). The motor efficiency is assessed in relation to reference values (5th, 15th and 50th percentiles) of national norms, the physical activity on the basis of target values (recommendations for physical activity of children and adolescents) and the body composition on the basis of international (IOTF) BMI cut-offs for the classification of children in overweight and obese. During the implement in physical education classes, 3 credit hours are required, immediate results and evaluations of the schoolchildren are provided and charts of their physical development indices are filed. These charts are diachronic and accompanying data of every schoolboy/schoolgirl in physical education. The inclusion of the proposed package in the curriculum of physical education and its application in this course are expected to contribute to raising awareness and sensitization among parents and schoolchildren, as well as to increase their care for the variance of indices in normal and "favorably" to health range.